Exposure to sewage water and the development of allergic manifestations in Finnish children. Issue 6 (28th June 2019) - Kujansuu, Eila; Kujansuu, Leena; Paassilta, Marita; Mustonen, Jukka; Vaarala, Outi
Abstract: Background: The hygiene hypothesis suggests that a decreased microbial load contributes to an increased risk of allergies. In the Finnish municipality of Nokia, sewage water was accidentally mixed with drinking water for 2 days. We studied the association between exposure and the emergence of allergies in children. Methods: Children aged 2‐5 years living in the accident area and an age‐matched cohort from the control municipality were recruited. Based on the questionnaires, we identified 139 children exposed to the contaminated water and selected age‐ and sex‐matched controls for them (mean age 16.59 months at the time of the accident). Allergic symptoms and diseases were recorded by ISAAC questionnaires and skin prick tests (SPTs) performed 2 and 5 years after the accident. Results: SPT positivity at 5 years of follow‐up was decreased in the children exposed to the sewage water below 1 year of age (OR 0.311, 95% CI 0.118‐0.820; P  = 0.019), particularly in children who did not develop gastroenteritis at exposure. In contrast, the children over 1 year of age at the exposure tended more likely to be SPT‐positive at 5 years of follow‐up (OR 1.997, 95% CI 0.963‐4.143; P  = 0.070). Conclusions: Sewage water exposure during the first year of life, but not later, decreased the risk of IgE sensitization emphasizing the importance of age as a modulator. The modulation of IgE sensitization by the presence of clinical gastroenteritis at the exposure suggests that the nature of microbial load may have importance or alternatively shared host defense mechanisms protect from infection and atopic sensitization. Abstract :